Shakespeare the complete works of William Shakespeare. - Shakespeare, William 1564-1616. (Portland, Or. Creative Multimedia Corporation, 1992)
American and Queen's English versions of the works of Shakespeare including full text of plays, poems, and sonnets. Features full text index, index browsing, and table of contents.
Title from disc label.
System requirements for IBM-compatible PC: 640K RAM; DOS 3.1 or later; Microsoft CD-ROM Extensions (MSCDEX) 2.0 or later; VGA graphic capabilities; CD-ROM drive. SuperVGA with 512KB video memory capable of 640x480x256 colors recommended.
System requirements for Macintosh computer: 2MB RAM; System 6.0.5 or greater; eight-bit color, thirty-two-bit QuickDraw graphics capabilities; color monitor; CD-ROM drive with CD-ROM extensions, ISO 9660 file access, and foreign file access.
Keywords: Shakespeare, William -- 1564-1616.